Strategi Pondok Pesantren Madinatul Qur'an Dalam Meningkatkan Jumlah Santri Baru Melalui Aplikasi Tik Tok di Desa Betung Ogan Ilir - Erisya Sawitri; Candra Darmawan; Emi Puspita Dewi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to determine the strategy of the Madinatul Qur'an Islamic Boarding School in increasing the number of new students through the use of the TikTok app in Betung Village, Ogan Ilir. In today's digital era, social media has become a crucial tool for expanding the reach of information and promotion, including for Islamic educational institutions. This study employed qualitative methods with a descriptive approach. Data were obtained through interviews, observations, and documentation with informants including the boarding school leadership, teachers, social media administrators, and students at the Madinatul Qur'an Islamic Boarding School. The results indicate that the Islamic boarding school's marketing strategy through TikTok involves showcasing student activities, religious activities, memorization programs, and the religious and disciplined atmosphere of the boarding school. Content is creatively curated, taking TikTok trends into account, to attract the interest of the younger generation. Although the school does not yet have a dedicated promotional team, social media management is carried out collaboratively by administrators and students under the direction of the boarding school leadership. The success of this strategy is supported by the involvement of students, alumni, and community support, who actively disseminate positive information about the boarding school. The impact of this strategy is evident in the increased interest of prospective new students who learn about the boarding school through social media, particularly TikTok. Thus, the use of TikTok has proven to be an effective means of promoting the positive image of the Madinatul Qur'an Islamic Boarding School while increasing the number of new students. The results of this study are expected to serve as a reference for other Islamic educational institutions in utilizing digital media as a creative and effective promotional strategy.